The Relationship between Learning Motivation and Self Efficacy among Nursing Students - Hassankhani Hadi; Mohajjel Aghdam Alireza; Rahmani Azad; Mohammadpoorfard Zeynab (Tabriz University of Medical Sciences, 2015)
Introduction: Self-efficacy and learning motivation are two important variables for professional learning, leading to academic success. Nursing students' learning motivation and self-efficacy have been considered in different studies separately, therefore this study aimed to investigate the relationship between self-efficacy and learning motivation among nursing students. Methods: This is a descriptive-correlational study, carried out at Tabriz University of Medical Sciences in 2013-14. Data was gathered with questionnaires about science motivation and self-efficacy for professional nursing competence and analyzed by descriptive and inferential statistics through SPSS software (version 13). Results: The learning motivation and self-efficacy of the nursing students was 67.89±14.12 and 68.10±14.50, respectively. There was a significant correlation between learning motivation and self-efficacy (P < 0.001). Conclusion: Due to the significant relationship between learning motivation and self-efficacy in professional nursing competency, it is suggested that an increase in learning motivation could be associated with the promotion of self-efficacy in professional nursing competency in nursing students.